Marketing strategies used for alternative protein products sold in Australian supermarkets in 2014, 2017, and 2021 - Brooker, Paige G.; Hendrie, Gilly A.; Anastasiou, Kim; Woodhouse, Rachel; Pham, Theresa; Colgrave, Michelle L. (Frontiers in Nutrition, 2022)
Marketing plays an important role in consumers’ perceptions and acceptance of new foods. The purpose of this study was to investigate the marketing strategies used for alternative protein products available in Australia in 2014, 2017 and 2021. Product data were extracted from FoodTrackTM, an established database of packaged supermarket products. Marketing strategies investigated included product format descriptors, front of pack (FOP) labelling claims, price, and in-store placement (2021 only). Data from 292 alternative protein products (n=12 tofu-based products; n=100 legume-based products; and n=180 plant-based meats) were analysed. Across the product range, ‘burgers’ (n=86), ‘strips and similar’ (n=51) and ‘sausages’ (n = 42) were the most common product formats, accounting for 61% of the product range. Nutrient content claims featured on 273 (93%) products. ‘Positive’ nutrient claims (those highlighting the presence of a nutrient) occurred on FOP labels four times more than ‘negative’ nutrient claims (those highlighting the absence or low levels of a nutrient; 432 versus 101, respectively). Protein-related claims were the most common ‘positive’ nutrient claim (n = 180, 62%). Health claims on FOP labels appeared on 10% of products. Most products (n = 265, 91%) mentioned a dietary pattern (such as ‘vegetarian’ and ‘plant-based’), or a combination of dietary patterns on their FOP label. The price of alternative products increased over time; between 2014 and 2021, on average, the unit price increased (9% increase, p = 0.035) and the pack size decreased (14% decrease, p < 0.001). There was inconsistency in product placement across the eight stores visited. Occasionally (n=3 of 13 locations), chilled alternative protein products were positioned near conventional meat products. More commonly, alternative protein products shared space with other vegetarian products (such as non-dairy cheeses and tofu blocks) or alongside convenience products, suggesting these products are promoted as convenience foods, or options for individuals with special dietary needs. This study provides a useful evidence base to understand the marketing strategies used for alternative protein products. It appears from this analysis that considerable effort has gone into providing consumers with a level of familiarity and comfort prior to purchasing these alternative protein products.